Manual of reproductive health care - Bhattacharya, Susmita (Jaypee Brothers Medical Publishers, 2014)
Women's health is a central part of the health of the nation. Reproductive health is an important aspect of women's health. The book is written with the aim of presenting reproductive health problems in relation to sociocultural and medical dimensions.